2019
DOI: 10.14740/jocmr3878
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Empathy and Burnout Among Emergency Medicine Physicians

Abstract: Background The association between physician self-reported empathy and burnout has been studied in the past with diverse findings. We aimed to determine the association between empathy and burnout among United States emergency medicine (EM) physicians using a novel combination of tools for validation. Methods This was a prospective single-center observational study. Data were collected from EM physicians. From December 1, 2018 to January 31, 2019, we used the Jefferson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 42 publications
0
34
1
1
Order By: Relevance
“…This is supported by at least one study showing that residents tend to have higher burnout scores compared with attending physicians. 49 The younger cohorts are at a life stage where they may be looking for a spouse, getting married and having children. However, at the same time, they also need to complete their postgraduate training and develop their career paths.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by at least one study showing that residents tend to have higher burnout scores compared with attending physicians. 49 The younger cohorts are at a life stage where they may be looking for a spouse, getting married and having children. However, at the same time, they also need to complete their postgraduate training and develop their career paths.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by other studies that used CBI to measure burnout. 19,20,[25][26][27][28][29][30] The EPs had a high score in the work-related domain, a domain that is highly associated with burnout in the ED. 17 The Pearson correlations showed a strong and statistically signi cant positive correlation between all three CBI burnout subscales and the SOS-S scale and its subscales (stress overload, personal vulnerability, and event load), such that when burnout increases, stress overload, personal vulnerability, and event load also increase (p<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“… 18 Other studies using different empathy tools showed a similar trend among residents of different training years. 6 , 21 Though we can still not fully understand the mechanism(s) for why these trends are similar, perhaps different patient illnesses (e.g., different acuity levels), patient trust in physicians or different stress levels, anxiety, or burnout among physicians could all affect physicians' empathy. 6 , 22 We should also consider that senior residents may have higher stress and burnout levels which could partially attribute to the decreased empathy levels 6 as compared to their junior counterparts.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Empathy can be measured either by health care providers themselves or by their patients. 5 , 6 High consistency has been reported between patient perception of provider empathy and patient satisfaction to the providers. 7 , 8 By far, one of the commonly used empathy measures is the Jefferson Scale of Patient Perception of Physician Empathy (JSPPPE).…”
Section: Introductionmentioning
confidence: 99%